Deep eutectic solvents vs. ionic liquids: similarities and differences - Sosa, Filipe H. B. (2022)
The extensive use of toxic and persistent solvents in chemical processes and products, and the awareness of their negative impact on environment and public health, have led to a growing interest from both research community and chemical industry on the topic of sustainable solvents. In this sense, two classes of “green” solvents, Ionic Liquids (IL) and Deep Eutectic Solvents (DES), have been studied as eco-friendly alternatives to increase the sustainability of chemical processes and products. The research on ILs and their applications can be traced back to the beginning of the 20th century but only accelerated in the last 20 years, while the concept of DES is quite recent as it was proposed for the first time in the beginning of this century. Equivocally, DES are often considered in literature as subclass of ILs. Despite the similarities between these solvents, mainly related to their applications and some physical properties, from a physicochemical point of view they are two distinct groups of solvents. Moreover, the countless number of combinations of precursors that can form IL and DES makes their characterization and benchmark usually difficult. Therefore, this chapter intends to clarify the definition and classification of these green solvents and stresses out the main differences, similarities, advantages and disadvantages between them. A series of comparisons between their physicochemical properties and other topics such as toxicity, biodegradability and recycling are herein tackled. In addition, the application of these solvents in the valorization of lignocellulosic biomass was briefly discussed as a case study with high potential for industrial implementation.